Methods and mechanical properties of polymer hybrid composites and hybrid polymer composites: influence of ionic liquid addition - Shamsuri, Ahmad Adlie; Md. Jamil, Siti Nurul Ain; Mohamed Yusoff, Mohd Zuhri; Abdan, Khalina (Multidisciplinary Digital Publishing Institute, 2023)
Polymer hybrid composites and hybrid polymer composites are distinct but interconnected composite classes, each with unique compositions and design philosophies. The mechanical properties of these composites are vital in advanced materials for their impact on performance, durability, and suitability for various applications. The addition of ionic liquids into these composites is a promising innovation in advanced materials. In this short review, various polymer matrices (e.g., thermosets, thermoplastics, and biopolymers), fillers (e.g., inorganic, carbon, organic, and metal), and ionic liquids (e.g., imidazolium- and phosphonium-based) used for fabricating polymer hybrid composites and hybrid polymer composites added with ionic liquids are identified. Furthermore, the addition of ionic liquids into these composites through different methods (e.g., magnetic stirring, mechanical stirring, solid grinding, etc.) is discussed. The influence of ionic liquid addition on the mechanical properties, specifically the tensile properties of these composites is also shortly reviewed. The changes in the tensile properties, such as tensile strength, tensile modulus, and elongation at break of these composites are explained as well. The information presented in this review enhances an understanding of the methods applied to add ionic liquids into polymer hybrid composites and hybrid polymer composites, along with their tensile properties. In short, some ionic liquids have the capacity to enhance the tensile properties of hybrid polymer composites, and several ionic liquids can reduce the tensile properties of polymer hybrid composites.